YfiBNR mediates cyclic di-GMP dependent small colony variant formation and persistence in Pseudomonas aeruginosa. - Jacob G Malone (Public Library of Science (PLoS), 2010)
During long-term cystic fibrosis lung infections, Pseudomonas aeruginosa undergoes genetic adaptation resulting in progressively increased persistence and the generation of adaptive colony morphotypes. This includes small colony variants (SCVs), auto-aggregative, hyper-adherent cells whose appearance correlates with poor lung function and persistence of infection. The SCV morphotype is strongly linked to elevated levels of cyclic-di-GMP, a ubiquitous bacterial second messenger that regulates the transition between motile and sessile, cooperative lifestyles. A genetic screen in PA01 for SCV-related loci identified the yfiBNR operon, encoding a tripartite signaling module that regulates c-di-GMP levels in P. aeruginosa. Subsequent analysis determined that YfiN is a membrane-integral diguanylate cyclase whose activity is tightly controlled by YfiR, a small periplasmic protein, and the OmpA/Pal-like outer-membrane lipoprotein YfiB. Exopolysaccharide synthesis was identified as the principal downstream target for YfiBNR, with increased production of Pel and Psl exopolysaccharides responsible for many characteristic SCV behaviors. An yfi-dependent SCV was isolated from the sputum of a CF patient. Consequently, the effect of the SCV morphology on persistence of infection was analyzed in vitro and in vivo using the YfiN-mediated SCV as a representative strain. The SCV strain exhibited strong, exopolysaccharide-dependent resistance to nematode scavenging and macrophage phagocytosis. Furthermore, the SCV strain effectively persisted over many weeks in mouse infection models, despite exhibiting a marked fitness disadvantage in vitro. Exposure to sub-inhibitory concentrations of antibiotics significantly decreased both the number of suppressors arising, and the relative fitness disadvantage of the SCV mutant in vitro, suggesting that the SCV persistence phenotype may play a more important role during antimicrobial chemotherapy. This study establishes YfiBNR as an important player in P. aeruginosa persistence, and implicates a central role for c-di-GMP, and by extension the SCV phenotype in chronic infections.